Survey of the costs of Peripheric Intravenous Device in the composition of the values of the internment in pediatrics unit - a quantitative study - Tathiana Martins; Zenith Rosa Silvino (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Observing in practical daily of the pediatric assistance the puncture of repetition1 for maintenance of a security access in the medicine administration with drawn out period and knowing that the system of payment to the hospital for the SUS (system of health financed by the government) is for type of illness, it sharpened me the interest in developing a exploratory, descriptive research with quantitative boarding on the costs of Peripheral Intravenous Device (DIP) in the internment in Pediatrics2. Objectives: To raise the costs of DIP used during the internment in a pediatrics unit; To identify the causes of substitution of DIP in the venous accesses during the internment in a pediatrics unit and To correlate the cost of DIP in the composition of the final remuneration of the paid pediatrics internments for the SUS. The scene of the research was a Pediatric Infirmary of a University Hospital (HU). Sample: nineteen children interned in the period of October of 2006 the April of 2007. The research was approved by the Committee of Ethics of the Institution under nº. 071/2006. The date had been analyzed statistical and organized in three categories: I. Demographic profile and Epidemiologist of the Children interned in the Infirmary of Pediatrics of the HU; II The Costs of the DIP in the Process of Hospitalization in Pediatrics in the HU; e III. The Costs of the DIP in the composition of the final remuneration of the paid pediatrics internments for the SUS. In the first category the characterization and the profile of the clientele interned in the Infirmary of Pediatrics had been presented. In the second category the main causes of the loss of a peripheral venous access had been presented, thus tracing a parallel with the average of time of duration of a venous access, the places of effective venous puncture and the deriving costs of the infusions imperfections. In the third category they had been presented the paid time of permanence for the SUS for each illness related to the real time of permanence of each customer, the costs of the venous accesses during the period of each internment and the costs of the DIP when compared with the costs of the internment. Age of preschool pertaining to school is concluded that the majority of the interned children was the masculine sort, resident it are of the city of localization of the HUAP, remaining interned in its majority for a period of 7 the 10 days or 21 the 30 days. Was used a average of 27,3 DIP for child, being the main cause of infusion imperfection the fleabite3;4. The average of permanence of the DIP was of 72 hours, evidencing that raised the quantitative expense of DIP directly was related to the inability and lack of technique of puncture of the nursing team. Had to the quantitative raised one of used DIP, the expenses of exactly in relation to the paid value of the internment for the SUS varied in 52% of the sample between R$25,00 the R$100, 00, many of the 19 times representing of up to 31% of the value received for the hospital for determined illness. Therefore, it urges to continue investigating in this line theoretician-methodological to favor the process of consolidation of the nursing as profession recognized and sanctioned by its components (the professionals) and its dependents (the population).